2021
DOI: 10.1111/rec.13415
|View full text |Cite
|
Sign up to set email alerts
|

Cultivars of popular restoration grass developed for drought do not have higher drought resistance and do not differ in drought‐related traits from other accessions

Abstract: Numerous functional traits have been identified as key contributors to plant performance under drought. However, many of these traits, specifically root traits, are rarely considered in the development of native plant cultivars. In this study, we assessed whether cultivars of the perennial grass Elymus trachycaulus (Slender wheatgrass) developed for drought differ in (a) drought resistance (i. e. a plant's ability to maintain aboveground biomass productivity under water deficit), (b) aboveground and belowgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…While the TRY Plant Trait database contains > 200 000 observations for seed mass, seed surface area and volume are reported far less frequently with no explicit mention of SSM; this is in stark contrast with widely reported values for massand area-standardized values of leaf and root traits ( Kattge et al 2020 ). Developing drought-tolerant perennial grasses for restoration has proven a challenging task, especially through the lens of identifying functional traits that confer stress tolerance ( Garbowski et al 2021 ). Sagebrush steppe restoration from seed is highly variable, and native species experience especially high failure rates ( Davies et al 2011 ;Clements et al 2017 ;Svejcar et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the TRY Plant Trait database contains > 200 000 observations for seed mass, seed surface area and volume are reported far less frequently with no explicit mention of SSM; this is in stark contrast with widely reported values for massand area-standardized values of leaf and root traits ( Kattge et al 2020 ). Developing drought-tolerant perennial grasses for restoration has proven a challenging task, especially through the lens of identifying functional traits that confer stress tolerance ( Garbowski et al 2021 ). Sagebrush steppe restoration from seed is highly variable, and native species experience especially high failure rates ( Davies et al 2011 ;Clements et al 2017 ;Svejcar et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research using high‐throughput genomics to develop predictive plant trait models shows considerable promise in rapidly accelerating selection and increasing the effectiveness of native plant materials (Jones et al 2022). Such efforts need to be broadened, as traditional plant breeding approaches often fail to release plant materials possessing the actual trait functionality needed to successfully restore degraded ecosystems (Garbowski et al 2021). An important and critical caveat is that genetic variation must exist within (native) plant species to be able to select for the desired trait(s) and the stability of gene expression conferring the trait must be independent of the environment (i.e.…”
Section: Application: Seeding and Breedingmentioning
confidence: 99%
“…Drought avoidance can also be a useful strategy, as demonstrated in a California annual grassland study where seedling root length (and presumably access to more persistent moisture) was positively related to seeding success during an exceptionally dry period (Harrison & LaForgia, 2019). A number of studies have also shown that preconditioning plants by exposing them to periodic drought before use in restoration can enhance transplant success (Kimball et al, 2017; Valliere et al, 2019), implicating a role for drought tolerance in mediating restoration outcomes, although this is not always the case (Garbowski et al, 2021). These and other studies suggest that controlled experiments linking metrics of drought responses to restoration outcomes could be valuable in identifying causal mechanisms of survival and candidate species that may perform well under arid conditions following restoration.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have also shown that preconditioning plants by exposing them to periodic drought before use in restoration can enhance transplant success (Kimball et al, 2017;Valliere et al, 2019), implicating a role for drought tolerance in mediating restoration outcomes, although this is not always the case (Garbowski et al, 2021).…”
Section: Introductionmentioning
confidence: 99%